Humoral response to conjugate pneumococcal vaccine in paediatric oncology patients. Issue 4 (25th November 2010) - Cheng, Frankie Wai Tsoi; Ip, Margaret; Chu, Yvonne Yuen Ling; Lin, Zheng; Lee, Vincent; Shing, Ming Kong; Leung, Wing Kwan; Yuen, Patrick Man Pan; Li, Chi Kong
Abstract : Objective: Pneumococcal conjugate vaccine (PCV) is an effective way to prevent invasive pneumococcal diseases in high risk populations. The efficacy of this vaccine in paediatric oncology patients remains unknown. Design and setting: The authors evaluated the antibody response to seven pneumococcal serotypes in paediatric oncology patients given two doses of heptavalent PCV (PCV-7). Results: Forty-four patients (20 males; 24 females) with median age 9.5 years were studied. After two doses of PCV-7, 86–100% of patients had protective antibody titres against the seven vaccine serotypes. Increases in geometric mean antibody concentrations ranged from 3.8-fold for serotype 19F to 85.8-fold for serotype 14. There was no documented invasive pneumococcal disease in our cohort during the study period. Conclusion: PCV can elicit protective antipneumococcal antibody responses in paediatric oncology patients.